CuS nanoparticles and camptothecin co-loaded thermosensitive injectable hydrogel with self-supplied H2O2 for enhanced chemodynamic therapy - Tang, Wenxue; Li, Xiang; Liu, Zeming; Meng, Lyu; Zhu, Daoming; Huang, Qinqin (Frontiers in Bioengineering and Biotechnology, 2022)
Chemodynamic therapy (CDT) is a kind of anti-tumor strategy emerging in recent years, but the concentration of hydrogen peroxide (H2O2) in the tumor microenvironment is insufficient, and it is difficult for a single CDT to completely inhibit tumor growth. Here, we designed a CuS nanoparticles (NPs) and camptothecin (CPT) co-loaded thermosensitive injectable hydrogel (SCH) with self-supplied H2O2 for enhanced CDT. SCH is composed of CuS NPs and CPT loaded into agarose hydrogel according to a certain ratio. We injected SCH into the tumor tissue of mice, and under the illumination, CuS NPs converted the near-infrared(NIR) laser into heat to realize photothermal therapy (PTT), and at the same time, the agarose hydrogel was changed into a sol state and CPT was released. CPT activates nicotinamide adenine dinucleotide phosphate oxidase, increases the level of H2O2 inside the tumor, and realizes the self-supply of H2O2. At the same time, CuS can accelerate the release of Cu2+ in an acidic environment and light, combined with H2O2 generated by CPT for CDT treatment, and consume glutathione in tumor and generate hydroxyl radical, thus inducing tumor cell apoptosis. The SCH system we constructed achieved an extremely high tumor inhibition rate in vitro and in vivo, presenting a new idea for designing future chemical kinetic systems.